Is dietary diversity an indicator of food security or dietary quality?: a review of measurement issues and research needs - Ruel, Marie T. (International Food Policy Research Institute, 2003)
Although dietary diversity is universally recognized as a key component of healthy diets, there is still a lack of consensus on how to measure and operationalize it. This paper focuses on the issues of dietary diversity in developing countries. It also draws upon experience from developed countries to address the following questions: 1. How is dietary diversity conceptualized, operationalized, and measured, and how does it relate operationally to dietary quality?; 2. Is there an association between dietary diversity and nutrient adequacy in developing countries? Between dietary diversity and child growth?; 3. What is the relationship between household-level dietary diversity and socioeconomic factors and food security?; 4. What key measurement issues need to be addressed to better operationalize and understand dietary diversity?